Effects of a partly self-administered exercise program before, during, and after allogeneic stem cell transplantation - Wiskemann, Joachim; Dreger, Peter; Schwerdtfeger, Rainer; Bondong, Andrea; Huber, Gerhard; Kleindienst, Nikolaus; Ulrich, Cornelia; Bohus, Martin (Blood, 2011)
Before, during, and after allogeneic hematopoietic stem cell transplantation (allo-HSCT), patients experience considerable physical and psychologic distress. Besides graft-versus-host disease and infections, reduced physical performance and high levels of fatigue affect patients' quality of life. This multicenter randomized controlled trial examined the effects of a partly self-administered exercise intervention before, during, and after allo-HSCT on these side effects. After randomization to an exercise and a social contact control group 105 patients trained in a home-based setting before hospital admission, during inpatient treatment and a 6- to 8-week period after discharge. Fatigue, physical performance, quality of life, and physical/psychologic distress were measured by standardized instruments at baseline, admission to, and discharge from hospital and 6 to 8 weeks after discharge. The exercise group showed significantly improvement in fatigue scores (up to 15% improvement in exercise group vs up to 28% deterioration in control; P < .01-.03), physical fitness/functioning (P = .02-.03) and global distress (P = .03). All effects were at least detectable at one assessment time point after hospitalization or repeatedly. Physical fitness correlated significantly with all reported symptoms/variables. In conclusion, this partly supervised exercise intervention is beneficial for patients undergoing allo-HSCT. Because of low personnel requirements, it might be valuable to integrate such a program into standard medical care.